2014
DOI: 10.1194/jlr.m051284
|View full text |Cite
|
Sign up to set email alerts
|

A novel activity of microsomal epoxide hydrolase: metabolism of the endocannabinoid 2-arachidonoylglycerol

Abstract: including environmental chemicals and many therapeutic drugs. This enzymatic action converts lipophilic and sometimes reactive epoxides to more polar 1,2-diols. It also activates (pro)toxins and (pro)carcinogens ( 1, 2 ). In addition to xenobiotic metabolism, EPHX1 regulates endogenous steroid metabolism ( 3 ), bile acid transportation ( 4 ), and the vitamin K1 reductase complex that is responsible for vitamin K1 oxide reduction activity ( 5 ). While a number of diverse functions of EPHX1 have been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The most active preparation was that of human mEH with an estimated turnover rate of 50 nmol arachidonic acid formed per milligram protein per minute. Because the activity reported by (Nithipatikom 2014 [1] ) for human mEH was several orders of magnitudes higher (see last paragraph of this section for a comparison), these results already demonstrate that mEH does not possess substantial 2-AG hydrolase activity. However, to clarify whether the measurable 2-AG hydrolase activity in our recombinant purified enzymes might be attributed to any impurities of the preparation rather than to mEH itself, we refined the analysis of enzymatic turnover in the presence and absence of 1,1,1-trichloropropene 2,3-oxide (TCPO), a potent mEH inhibitor.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…The most active preparation was that of human mEH with an estimated turnover rate of 50 nmol arachidonic acid formed per milligram protein per minute. Because the activity reported by (Nithipatikom 2014 [1] ) for human mEH was several orders of magnitudes higher (see last paragraph of this section for a comparison), these results already demonstrate that mEH does not possess substantial 2-AG hydrolase activity. However, to clarify whether the measurable 2-AG hydrolase activity in our recombinant purified enzymes might be attributed to any impurities of the preparation rather than to mEH itself, we refined the analysis of enzymatic turnover in the presence and absence of 1,1,1-trichloropropene 2,3-oxide (TCPO), a potent mEH inhibitor.…”
Section: Resultssupporting
confidence: 51%
“…With respect to the observations made by (Nithipatikom 2014 [1] ), we suggest as an alternative explanation that mEH might activate a so far uncharacterized MAFP-sensitive 2-AG hydrolase.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The sEH, on the other hand, appears to have a rather restricted substrate selectivity being involved in the metabolism of endogenous epoxides and has not been shown to hydrate any toxic or mutagenic xenobiotics (Morisseau and Hammock, 2013). Although phosphatase activity was recently reported for sEH and mEH was shown to have esterase activity in the metabolism of endogenous substrates (De Vivo et al, 2007;Nithipatikom et al, 2014), to our knowledge, xenobiotic substrates of mEH are limited to three-membered cyclic ethers (i.e., epoxides). In this study, we show for the first time the mEH-catalyzed hydration of an oxetanyl ring that is part of the spiro oxetanylazetidinyl moiety of AZD1979.…”
Section: Discussionmentioning
confidence: 99%
“…Androstene oxide and epoxyestratrienol were shown to be endogenous EPHX1 substrates (Vogel-Bindel et al 1982, Newman et al 2005). Recently, it was reported that EPHX1 metabolizes endocannabinoid 2-arachidonoylglycerol to free arachidonic acid and glycerol (Nithipatikom et al 2014). Thus, EPHX1 may play an important role in the endocannabinoid signaling pathway and modulate, through its dysregulation, energy metabolism and immunity.…”
Section: Ephx1 Enzyme Functionmentioning
confidence: 99%